Detection of Fima and Fimh Genes in Klebsiella pneumoniae Isolated from Necrotizing Enterocolitis Patients in Infants - Luma Abdalhady Zwain (Journal of Global Pharma Technology, 2016)
Sixty-four clinical isolates were collected from the children's protection hospital by Medical city in Baghdad for children infected with Necrotizing Enterocolitis where included (41) samples belong to stool and (14) samples belong to blood and (9) samples belong to urine for the period of 29/1/2018 to 4/4/2018. All the samples were cultured on MacConkey agar and Blood agar for the purpose of diagnosis.  All isolates were identification depending on macroscopic, microscopic, biochemical tests and definite with Vitek-2 compact system, forty three isolates were obtained from all samples, (26) isolates as K. pneumoniae (60.46%) and 8 isolates as E. coli (18.60%) and 4 isolates as P.aeruginosa (9.30%) and 2 isolates were K.oxytoca (4.65%) and 2 isolates were E. cloacae (4.65%) and 1 isolates was P. hauseri (2.32%). The results showed that K. pneumoniae was the predominant in the samples which taken from infants infected to Necrotizing Enterocolitis. In these study, oame of virulence genes have been investigated for K.pneumoniae included both fimA and fimH gens which encodes for the fimbriae adhesion protein that belonging to type 1 fimbriae named Fim protein, and the results showed presence of fimA and fimH genes (100 %).Keywords: Klebsiella pneumoniae, Isolation, Identification, Necrotizing, Enterocoliti, fimA, fimH.